Proceedings of the Thirty-Sixth Annual ACM Symposium on Theory of Computing 2004
DOI: 10.1145/1007352.1007379
|View full text |Cite
|
Sign up to set email alerts
|

Exponential separation of quantum and classical one-way communication complexity

Abstract: Abstract. We give the first exponential separation between quantum and bounded-error randomized one-way communication complexity. Specifically, we define the Hidden Matching Problem HMn: Alice gets as input a string x ∈ {0, 1} n and Bob gets a perfect matching M on the n coordinates. Bob's goal is to output a tuple i, j, b such that the edge (i, j) belongs to the matching M and b = x i ⊕ x j . We prove that the quantum one-way communication complexity of HMn is O(log n), yet any randomized one-way protocol wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
135
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 23 publications
3
135
0
Order By: Relevance
“…Another example is the CHSH game, where we can assume that both Alice and Bob win 1 point if the parity of their outputs is equal to the logical AND of their inputs, and they lose 1 point otherwise (see Example 1 in [6]). In fact, other known nonlocal games, including the GHZ-Mermin game [10], the Magic Square Game [11,12], the Hidden Matching game [13,14], Brunner and Linden's three games [6], are all examples of common interest games [25].…”
mentioning
confidence: 99%
“…Another example is the CHSH game, where we can assume that both Alice and Bob win 1 point if the parity of their outputs is equal to the logical AND of their inputs, and they lose 1 point otherwise (see Example 1 in [6]). In fact, other known nonlocal games, including the GHZ-Mermin game [10], the Magic Square Game [11,12], the Hidden Matching game [13,14], Brunner and Linden's three games [6], are all examples of common interest games [25].…”
mentioning
confidence: 99%
“…It has been shown that in the bounded-error model, any classical protocol requires Ω( √ n) bits of communication [11]. It was also shown in Ref.…”
Section: Quantum Communication Complexitymentioning
confidence: 76%
“…Likewise, quantum communication complexity studies the case where the parties are allowed to employ quantum resources such as quantum channels and shared entanglement [2,26]. Remarkably, it has been proven that there exist various problems for which the use of quantum resources offer exponential savings in communication compared to their classical counterparts [8][9][10][11]27]. In this section, our goal is to employ the mapping to construct protocols that can be implemented using only coherent states and linear optics.…”
Section: Quantum Communication Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…The scheme was based on hidden matching quantum retrieval games (QRGs), first introduced in Ref. [27]. Nevertheless, the scheme could not be considered practical, as the security analysis did not include the effects of noise.…”
Section: Introductionmentioning
confidence: 99%